Seasonal dynamics of heavy metal bioaccumulation (Fe, Mn, Cu, Zn and Pb) in Phragmites australis (Cav.) Trin. ex Steud. in Bardača fishpond - Maksimović Tanja (Kragujevac Journal of Science, 2019)
Paper monitors seasonal dynamics of heavy metals bioaccumulation (Fe, Mn, Cu, Zn and Pb) of emerged plant Phragmites australis (Cav.) Trin. ex Steud. on two localities (Necik and Sinjak) in the area of Bardača fishpond (BiH-Republic of Srpska). Dynamics of heavy metals bioaccumulation varied depending on sampling period, locality and plant organ. Concentration, transfer (transport) and accumulation of metals from sediment to rhizome above ground plant part was evaluated based on biological concentration factor (BCF), translocation ability (TA) and bioaccumulation factor (BAC). The highest average BCF value in researched species was determined for Fe (0.87) and the lowest for Zn (0.18). Bioaccumulation coefficient was the highest for Mn (0.82) and the lowest for Fe (0.20) whereas TA was the highest for Zn (2.28) and Mn (2.70). For Fe, it was significantly lower (0.24). Based on values for BCF, TA and BAC, Phragmites australis (Cav.) Trin. ex Steud. could be identified as accumulator for Mn and indicator for metals Fe, Zn and Cu and it has good potential for application in phytoremediation techniques, especially in phytostabilization and phytoextraction of polluted land. Considering the fact that higher degree of bioaccumulation was recorded in the period at the end of season, we could take this period as a signal for their removal from water ecosystems.